Efficient ecofriendly synthesis of pyrazole acryloyl analogs by amino acid catalysis. Issue 8 (17th April 2016) - Chaudhry, Faryal; Asif, Nadia; Shafqat, Syed Salman; Khan, Amir Azam; Munawar, Munawar Ali; Khan, Misbahul Ain
ABSTRACT: An easy and effective green approach of Knoevenagel condensation and arylidene formation with the substrates involves pyrazole-3-carbaldehydes and active methylenes under catalytic action of glycine (the simplest amino acid) in dimethylsulfoxide. These reactions were successfully carried out at room temperature. GRAPHICAL ABSTRACT: